Shape optimization of a snowboard sidecut geometry - Caillaud, B.; Gerstmayr, J. (Sports Engineering, 2022)
The distribution of the contact pressure occurring under the edge of a snowboard during a carved turn is a key factor influencing the riding behaviour. These interface loads are determined by the structural design, and in particular by the sidecut geometry of the edge line. In this study, the following inverse problem was set under investigation: if a certain interface pressure distribution is wished, how can the corresponding initial geometry of the snowboard be determined? A structural optimization strategy was presented, involving parametric B-spline representation of the sidecut geometry, finite element modeling of the composite structure deforming against a rigid surface, frictional contact formulation and derivative-free algorithm. A sidecut geometry leading to a contact pressure uniformly distributed along the sidecut line was sought, to illustrate the capabilities of the method. An actual snowboard prototype was made according to the outcome of the optimization, and an experimental validation was conducted to measure the physical pressure distribution and assess the accuracy of the numerical predictions. With the proposed method, the design can be controlled by the state variables of the deformed structure rather than the initial design variables, thus providing an alternative shortcut to the classical trial and error development strategies.